USE OF SOLAR ENERGY IN HEATING AND HOT WATER SUPPLY SYSTEMS (Academia Science Repository, 2023)
This article discusses the possibilities of using solar energy in heating systems. The advantages and disadvantages of solar heating systems are outlined. The types of solar collectors are analyzed and recommendations for their use are presented.